2003
DOI: 10.1002/14651858.cd000008.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for chronic asthma

Abstract: Unclear risk Withdrawal data are not described Free of other bias? Unclear risk No information available on the level of training of the therapist Christensen 1984 Methods Design: parallel group Allocation concealment: unclear Dias 1982 Acupuncture for chronic asthma (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 42 publications
0
50
2
7
Order By: Relevance
“…One Cochrane review (36) and two non-Cochrane reviews (9,17) assessed the efficacy of acupuncture for asthma comprising six RCTs (275 participants) with no meta-analysis performed. The authors concluded that no robust evidence exists to support acupuncture as being effective for treating childhood asthma.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…One Cochrane review (36) and two non-Cochrane reviews (9,17) assessed the efficacy of acupuncture for asthma comprising six RCTs (275 participants) with no meta-analysis performed. The authors concluded that no robust evidence exists to support acupuncture as being effective for treating childhood asthma.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…It consists of the stimulation of defined points on the skin (mostly by insertion of needles). Acupuncture has traditionally been used to treat asthma in China and is used increasingly for this purpose internationally (McCarney et al, 2004). It is thought that such treatments can correct any imbalances in vital life energy (perhaps along the lung, spleen, or kidney system meridians) that may be triggering the breathing problems.…”
Section: Asthma Treatmentmentioning
confidence: 99%
“…29 For psychological conditions, there was insufficient evidence in 2008 to recommend acupuncture for depression and trials demonstrated a high risk of bias 30 ; more recently a non-Cochrane review concluded that acupuncture is promising for anxiety and depression. 31 For respiratory conditions, in 2004 there was insufficient evidence to conclude whether or not acupuncture was effective for chronic asthma 32 ; a non-Cochrane review came to the same conclusion about allergic rhinitis 33 ; since then one large high-quality trial suggests that acupuncture has significant clinical benefit in seasonal allergic rhinitis. 34 Most of these non-pain conditions are hardly mentioned in CAP's advice (table 1).…”
Section: Comparing Leaflets With the Extant Evidence And Advertising mentioning
confidence: 99%